Transversal and transferable abilities. Understanding worker agency in contemporary advanced economies - Winch, Christopher [Verfasser] (My University, 2022)
„Workplace competence involves much more than the exercise of skills. Workers are expected to solve problems, plan, co-ordinate, communicate and evaluate their work and to manage projects with fellow workers including workers in different occupations. Their action is expected to display independent agency and thought. Jointly these abilities are integrated into an overarching occupational competence. But how does one give an account of these abilities without falling back on a reductive account in terms of skills? The distinction between Fähigkeiten and Fertigkeiten within German VET provides an important clue. These abilities can be realised in different ways through different skill sets and they also imply a focus on an aim such as project completion rather than on the exercise of skills in the performance of tasks. This presentation analyses what abilities besides skills are necessary in successful problem solving, project management, self-management and teamwork to give such an account of occupational competence. The dangers of describing workplace competence by assembling it from tasks rather than starting from an overarching concept of competence and then analysing its components are illustrated by comparing practice in some European countries with innovations (now largely abandoned) such as the NVQ in England.“ (author's abstract; BIBB-Doku)

„In seinem Beitrag analysiert Christopher Winch eine zentrale Zieldimension aktueller Gestaltungsansätze in der beruflichen Bildung, und zwar den Begriff „competence“. Mittels sehr unterschiedlicher theoretischer Bezüge, einschließlich curriculum- und berufsbildungstheoretischer Reflexionen und Überlegungen zur Autonomie am Arbeitsplatz, vergleicht er verschiedene Kompetenzkonzepte in Europa, die der Weiterentwicklung der Berufsbildung dienen. Winch fokussiert damit zum einen die sehr relevante didaktische Dimension und zum anderen die Rolle der Arbeitsorganisation für den internationalen Vergleich in der Berufsbildungsforschung.“ (Hrsg.; BIBB-Doku)
Keywords: G 1.2.3.1 Potenziale; L 2.3.2 Handlungs- & problemorientierte Methoden; G 2.3.1 Arbeitsteilung & -organisation; 370; Kompetenz; Kompetenzbegriff; Fähigkeit; Fertigkeiten; Begriff; Problemlösen; Arbeitsorganisation; Europäischer Qualifikationsrahmen; Vergleichende Berufsbildungsforschung; Internationaler Vergleich